Cutaneous side effects of TNF‐alpha inhibitors. (March 2017) - Lindhaus, Claudia; Tittelbach, Jörg; Elsner, Peter
Summary: Since the early 1990s, tumor necrosis factor alpha (TNF‐alpha) inhibitors have been successfully used in the treatment of various immune‐mediated inflammatory diseases. By now, comprehensive safety data has been compiled. While adverse reactions do occur, they are – in relation to the frequent use of these agents – rare and usually not serious. Cutaneous side effects include local injection site reactions, infections, immune‐mediated reactions, and neoplasms. The most common serious adverse events are of an infectious nature. Mycobacteria but also non‐mycobacterial pathogens, such as viruses and fungi, may cause serious, even lethal, systemic infections. The present article is meant to review current knowledge with respect to cutaneous side effects of TNF‐alpha inhibitors.